Analisis SWOT potensi halal tourism di Indonesia dengan NVivo: Studi literature review - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Nur Science Institute, 2024)
Indonesia has great potential in terms of tourism, both natural and cultural. However, there is still little tourism potential according to Sharia principles. This research aims to determine a SWOT regarding the potential for halal tourism in Indonesia. This research uses a qualitative method with NVivo and a literature review.